1995
DOI: 10.1136/gut.36.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic fluid gamma interferon concentrations and adenosine deaminase activity in tuberculous peritonitis.

Abstract: The y interferon (,y-IFN) concentration and the adenosine deaminase (ADA) activity were evaluated in 30 patients with tuberculous peritonitis, 21 patients with ascites due to a malignant disorder, and 41 patients with cirrhosis. The y-IFN concentrations were significantly higher (p<0.0001) in tuberculous peritonitis patients (mean: 6-70 U/ml) than in the malignant (mean: 3.10 U/ml) and cirrhotic (mean: 3.08 U/ml) groups. Use of a cut off value of ¢3.2 U/mli gave the assay a sensitivity of93% (25 of 27), a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 11 publications
(3 reference statements)
2
46
1
3
Order By: Relevance
“…In the present work, AFB smears were positive for only 3 of 14 (21.4 %) patients with a final clinical diagnosis of TB peritonitis, thus underpinning the insufficiency of this diagnostic technique. Further, Sathar et al (1995) found that ZN-stained AFB smears yielded negative results in all patients in their study. In contrast, Portillo-Gó mez et al (2000) found that ZN-stained AFB smears were positive for six of seven (85.7 %) patients tested.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the present work, AFB smears were positive for only 3 of 14 (21.4 %) patients with a final clinical diagnosis of TB peritonitis, thus underpinning the insufficiency of this diagnostic technique. Further, Sathar et al (1995) found that ZN-stained AFB smears yielded negative results in all patients in their study. In contrast, Portillo-Gó mez et al (2000) found that ZN-stained AFB smears were positive for six of seven (85.7 %) patients tested.…”
Section: Discussionmentioning
confidence: 77%
“…The development of techniques that are rapid and less invasive and that have high sensitivities, specificities, PPVs and NPVs would aid in the diagnosis of TB peritonitis and the swift initiation of treatment (Shawar et al, 1993;Sathar et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…36 Gamma (γ) interferon, secreted by antigen-triggered CD4+ lymphocytes, is a key lymphokine that activates macrophages, increasing their bactericidal activity against Mycobacterium tuberculosis. 34 Although the sensitivity and specificity of ascitic fluid ADA and γ-interferon activity are high in tuberculous peritonitis, their activities have been reported to be significantly lower in patients with low ascitic fluid protein concentration and in patients with AIDS, explained by a low lymphocyte activity due to the CD4+ lymphocyte depletion in HIV infection. 13,34 Serum CA-125 level may be raised in tuberculous peritonitis, but the test is not specific because other conditions can give rise to the level e.g.…”
Section: Diagnosis Of Abdominal Tuberculosismentioning
confidence: 98%
“…34 Although the sensitivity and specificity of ascitic fluid ADA and γ-interferon activity are high in tuberculous peritonitis, their activities have been reported to be significantly lower in patients with low ascitic fluid protein concentration and in patients with AIDS, explained by a low lymphocyte activity due to the CD4+ lymphocyte depletion in HIV infection. 13,34 Serum CA-125 level may be raised in tuberculous peritonitis, but the test is not specific because other conditions can give rise to the level e.g. carcinoma of the ovaries, though the decreasing CA-125 level is useful to evaluate the efficacy of therapy in TB peritonitis.…”
Section: Diagnosis Of Abdominal Tuberculosismentioning
confidence: 98%
See 1 more Smart Citation